A Mayer-Rokitansky-Kuster-Hauser patient with leiomyoma and dysplasia of neovagina: a case report - Varpu Jokimaa; Johanna Virtanen; Harry Kujari; Seija Ala-Nissilä; Virpi Rantanen (BMC, 2020)
Abstract Background Most patients with congenital uterus and vaginal aplasia (i.e., Mayer-Rokitansky-Kuster-Hauser [MRKH] syndrome) have rudimentary pelvic uterine structures that contain smooth muscle. Although leiomyomas and dysplasia of vaginal mucosa are relatively common in the general population, they are rare in MRKH patients. Data on the vulnerability of neovaginas to HPV-associated dysplasia are limited. Case presentation A rare case of an MRKH patient with two gynaecological conditions detected during long-term gynaecological follow-up is presented. At the age of 21, the patient was treated for HPV-associated neovaginal dysplasia. At the age of 47, a pelvic leiomyoma was detected with transvaginal ultrasound and confirmed with magnetic resonance imaging. Conclusion A Pap smear or human papillomavirus testing is indicated in sexually active MRKH women. Uterine rudiments contain smooth muscle, which facilitates the development of oestrogen-dependent diseases, such as leiomyomas and adenomyosis. Although magnetic resonance imaging is recommended in cases of a pelvic mass, easily attainable and cost-efficient transvaginal ultrasound offers high diagnostic accuracy in patients with a surgically created neovagina and is suitable for the patients' follow-up. Guidelines for the gynaecological follow-up of MRKH patients are warranted.